Implementasi Keadilan Gender dalam Putusan Pengadilan - Aliyah, Violita Fijannatin; Muhlashin, Firza Amanah; Rabbani, Adifa Zuhdi; Wahyudi, Indra; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The issue of gender justice in the Indonesian justice system continues to be a major concern amidst various legal reform efforts. This study aims to analyze the extent to which the principle of gender justice is implemented in court decisions, especially in cases involving women as plaintiffs, defendants, witnesses, or victims. This study uses a qualitative method with a normative-empirical approach, namely through a literature study of regulations and court decisions and supported by field data from interviews and relevant documents. Five main references are used as the basis for the analysis, including the implementation of PERMA No. 3 of 2017, jurisprudence practices in the Banyumas and Purwokerto Religious Courts, and a case study at the Banda Aceh Sharia Court. The results of the study show that although normatively the principle of gender equality has been accommodated in the constitution, national law, and ratified international instruments, in practice there are still inequalities. Several judges show gender sensitivity in their legal considerations, but not a few still maintain biased, demeaning, or even discriminatory views of women in the courtroom. PERMA No. 3 of 2017 is considered a strategic instrument, but its implementation still faces structural, cultural, and capacity constraints of the judicial apparatus. The conclusion of this study emphasizes the importance of strengthening the capacity of judges and court officials in implementing a gender justice perspective, as well as the need for continuous evaluation of the implementation of established judicial guidelines. Recommendations are directed at the need for reformulation of legal education, gender-responsive judicial oversight, and inter-institutional collaboration to encourage the creation of a fairer and more equal justice system for all parties.